Relationship between Library Usage and Perceived Academic Performance of TESDA Diploma Trainees: Basis of Research-Based Intervention Plan - Agway, Jovie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study sought to determine the correlation between library use and the perceived academic achievement of TESDA Diploma trainees at the main campus of the Cordillera State Institute of Technical Education (CSITE) and to assess the association of library use with educational achievement in competency-based Technical-Vocational Education and Training (TVET). The study adopted a quantitative correlational design to survey 106 first- to third-year trainees in the Diploma in Culinary Arts and the Diploma in Hospitality and Supervision, using stratified random sampling. Data were analyzed via descriptive statistics and Spearman’s Rho correlation. The results showed that the library was not used frequently but was used purposefully. Trainees reported high perceived academic performance on all parameters. Perceived academic accomplishment was not substantially associated with frequency of library use or total time spent in the library. However, the purpose of library use and the level of participation were marginally statistically significantly connected. Perceived academic success was also weakly but substantially associated with library utilization during the assessment phase. These results imply that the quality and goal of library engagement are significantly more critical than the quantity or duration of use, a crucial finding for how TVET institutions build and embed library services within competency-based curricula. A research-based intervention plan is presented to improve participation and to incorporate library services more deliberately in training and assessment. It is recommended that future research consider mixed-methods or longitudinal designs to overcome the limitations of cross-sectional surveys by collecting data on motivational, instructional, and digital literacy factors.